Pengaruh Kualitas Produk, Promosi dan Persepsi Harga Terhadap Kepuasan Pelanggan di De’ Margo Restaurant The Margo Hotel Depok - Faris Rifki Abdillah; Salman Paludi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The objective of this study is to investigate how product quality, promotion, and price perceptions impact customer satisfaction at de' MARGO Restaurant in The Margo Hotel Depok. The research was conducted during February to March 2023, and a quantitative method using primary data was employed. The sample consisted of 100 respondents, selected randomly through an accidental sampling method, who had purchased products from the restaurant. Only customers who had visited the restaurant at least twice were included in the data collection process, which involved filling out a questionnaire. The validity and reliability of the collected data were assessed through tests. IBM SPSS 26 software was used to perform multiple linear regression analysis, along with correlation coefficient and determination analysis. The results indicate that product quality has a partial impact on customer satisfaction, whereas promotion and price perceptions do not have a partial impact. However, when considered collectively, product quality, promotion, and price perceptions do have an influence on customer satisfaction.